4x-5x+3=14x

Simple and best practice solution for 4x-5x+3=14x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-5x+3=14x equation:


Simplifying
4x + -5x + 3 = 14x

Reorder the terms:
3 + 4x + -5x = 14x

Combine like terms: 4x + -5x = -1x
3 + -1x = 14x

Solving
3 + -1x = 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
3 + -1x + -14x = 14x + -14x

Combine like terms: -1x + -14x = -15x
3 + -15x = 14x + -14x

Combine like terms: 14x + -14x = 0
3 + -15x = 0

Add '-3' to each side of the equation.
3 + -3 + -15x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -15x = 0 + -3
-15x = 0 + -3

Combine like terms: 0 + -3 = -3
-15x = -3

Divide each side by '-15'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| 7cos-1=0 | | 2y+3=25 | | x=2y^2+6y | | -12x^2+4x+6=0 | | (x-4)2+(y-8)2= | | 49-x^2=log(x^2+10x+25) | | 7x-3(x-2)=2(2-c) | | 180=7x+5x | | x(x-13)= | | x+1+2x=10 | | g^2+2g-8=0 | | 2+x(23-7)=40 | | x+(x+2)+(x+4)+(x+6)=136 | | 3=b*3 | | g^2-49g=0 | | 35=-3+5(x+6) | | 9z+35=125 | | 3y-8=28 | | -5x+40=-25+87x | | 190=111-x | | 16-w=175 | | 25=6r+1 | | 4y^3-7y^2-16y+28= | | 35.9x+7.19y=31.595 | | -55x-65=71+6x | | -14=7(-3+n) | | -8(3+n)=32 | | -56=-7(p-7) | | -63x+89=22-63x | | -16=3+n | | 9x^2+3=147 | | 7x^2-105-0=0 |

Equations solver categories